Current and Future Therapies for Idiopathic Pulmonary Fibrosis. Issue 1 (December 2015) - Spagnolo, Paolo; Bonella, Francesco; Vasakova, Martina; Kreuter, Michael; Maher, Toby
Abstract Idiopathic pulmonary fibrosis (IPF) is the most common form of fibrosing idiopathic interstitial pneumonia. The disease, which primarily occurs in older adults, is inexorably progressive with a 5-year survival of approximately 20%. Improved understanding of disease pathobiology has affected the approach to treatment. Indeed, originally thought to be a chronic inflammatory disorder, IPF is now considered the result of persistent alveolar epithelial micro-injury followed by an aberrant repair response. This paradigm shift along with significant improvement in disease definition and patient stratification has led to an exponential increase in the number of high-quality clinical trials, most of which, however, have produced negative results, probably due to the multitude of cell types, growth factors and signaling pathways involved in the fibrotic process. Therefore, until recently IPF has lacked effective therapies. Finally, in 2014, pirfenidone, a compound with broad antifibrotic, anti-inflammatory and antioxidant properties and nintedanib, an orally available, small-molecule tyrosine kinase inhibitor with selectivity for vascular endothelial growth factor, platelet-derived growth factor and fibroblast growth factor receptors, have shown to significantly slow functional decline and IPF disease progression with an acceptable safety profile. This is a major step forward. However, neither pirfenidone nor nintedanib is a cure for IPF; neither drug improves lung function and the disease continues to progress in most patients despite treatment. A number of agents with high potential are currently being tested and many more are ready for clinical trials. Their completion is critical for achieving the ultimate goal of curing this devastating disease.